Variation and covariation in birthcoat and fleece traits of Drysdale sheep with reference to early selection and sampling positions : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University, New Zealand - Elgabbas, Hassanein Mohamed (Massey University, 1986)
Samples from different body regions were obtained from the birthcoat, first, second and third fleeces of sheep in two Drysdale flocks. Fibre type arrays of birthcoat samples were analysed and various wool traits were assessed and measured in samples obtained at three shearings. Sampling position was the main source of variation in most traits studied. Sex, birth rank, and age of dam generally made little contribution to the total variance. Shearing, flock and sire effects were also important sources of variation for many traits. The interaction of shearing X position and the interactions of sire with each of shearing, sex and birth rank were significant for many traits. Phenotypic correlations among fleece traits were estimated from shoulder and mid-side positions as well as among fleece averages calculated from all positions. Correlations among fleece averages showed that higher kemp score (KS) was associated with higher bulk; BUL (0.24 to 0.64), resilience; RES (0.03 to 0.48) and tristimulus colour values; X, Y and Z (0.08 to 0.46). Softer handle grade tended to be correlated with lower BUL (-0.22 to -0.66) and RES (-0.16 to -0.53) and higher lustre; LG (0.10 to 0.62). Higher medullation index (MI) was generally associated with higher BUL (-0.15 to 0.49) and tristimulus colour values (-0.01 to 0.60) and lower LG (-0.65 to 0.08). Correlations among tristimulus colour values were the highest between X and Y reflectances (0.93 to 1.00). Greasy and clean wool per unit area (GWA and CWA) were highly correlated (0.93 to 0.96). Heavier first greasy fleece weight (GFW1) correlated positively with GWA (0.59) and CWA (0.56). Staple length (STL) tended to be longer as GWA (0.37 to 0.60), CWA (0.39 to 0.60) and GFW1 (0.64) inceased and as BUL decreased (-0.01 to -0.54). BUL and RES were highly correlated (0.82 to 0.95). LG was negatively correlated with BUL (-0.12 to -0.66) and RES (-0.10 to -0.41). Very few sickle fibres were found in Drysdale materials; most arrays were plateau. Coarser arrays were associated with higher proportions of hairy-tip curly-tip fibres (HTCT). GFW1 increased as HTCTs increased (0.33 to 0.46). Generally, the correlations among birthcoat and third fleece traits were not strong which implies that birthcoat traits are not reliable indications to selection for various traits in later fleeces of Drysdale sheep. Higher MI was associated with coarser arrays (-0.07 to -0.55) and higher proportions of super-sickle A fibres (0.22 to 0.41). Finer arrays were associated with higher yield (0.01 to 0.38). In one flock, sheep with a higher proportion of halo-hair (HH) fibres had higher GWA (0.25 to 0.33), CWA (0.17 to 0.30) and heavier third fleece weights (0.09 to 0.33) while sheep with coarser birthcoat arrays showed a slight tendency to have more bulky fleeces (-0.22 to -0.29). Medullation index of the third fleece (MI3) as well as greasy and clean third fleece weights (GFW3 and CFW3) can be predicted, with limited accuracy (R2 = 0.50) from the first shearing shoulder (SH1) traits by using the following multiple regression equations: Within flock-sex groups MI3 = 9.15 + 0.45MI (SH1) + 1.84KS (SH1) For rams GFW3 = -1.47 + 0.04HH% (SH1) + 0.14X (SH1) - 0.09Z (SH1) CFW3 = -1.53 + 0.03HH% (SH1) + 0.14X (SHI) - 0.09Z (SH1) It appeared that the shoulder is the best position from which to sample fleeces when a number of traits are to be assessed for ranking Drysdale sheep.
Irregular pagination: missing page 99
Keywords: Wool; Sheep; New Zealand